PENERAPAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN MATEMATIKA YANG BERHUBUNGAN DENGAN BANGUN DATAR DAN BANGUN RUANG DI KELAS V SD - Nia Ainun Akhiriyah; Deri Fadly Pratama (COLLASE (Creative of Learning Students Elementary Education), 2019)
ABSTRACTThe author's background to do this research is to find out the lack of mathematical values and the low level of student learning activities in solving problems related to getting up flat and building space.Problem solving is carried out systematically using the Discovery Learning learning approach on material that is flat and constructed in the fifth grade of SDos Baros Mandiri 5 academic year 2018/2019. The research conducted is a type of classroom action research (CAR) consisting of 2 cycles, in which each phase has several stages.First, the planning phase, the second implementation / action, the third observation and finally the reflection phase. This research was directed to find out how the teaching process of Mathematics about solving problems related to flat building and building simple spaces with Discovery Learning models in class V of SDN Baros Mandiri 5. In addition, to find out how Mathematics learning outcomes about problem solving flat and simple space building with Discovery Learning models in class V students of Baros Mandiri Elementary School 5.Keywords: Discovery Learning Model, elementary school mathematics learning outcomes, elementary school students.